1990
DOI: 10.2105/ajph.80.2.150
|View full text |Cite
|
Sign up to set email alerts
|

HIV seropositivity of needles from shooting galleries in south Florida.

Abstract: Needle/syringe combinations were collected from three shooting galleries in South Florida and tested for the presence of antibodies to HIV-1. Fifteen of 148 needles (10.1 percent) tested positive for HIV-1 antibody. Seropositivity rates did not vary by the day of the week of collection, nor by shooting gallery from which they were collected. When the needle appeared to contain blood residue, 20.0 percent were positive versus 5.1 percent with no blood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(30 citation statements)
references
References 3 publications
1
27
0
2
Order By: Relevance
“…Juarez suggests that venue-based interventions in shooting galleries may be especially useful for reaching high risk male IDUs in an effort to reduce the spread of blood borne infections. A previous study by our group and other international literature have documented that shooting galleries are closely associated with risky injection practices including the sharing and renting of used syringes (Celentano et al, 1991;Chitwood et al, 1990;Reyes et al, 1996). All of the male IDUs in both study sites reported having shared syringes in shooting galleries.…”
Section: Discussionmentioning
confidence: 76%
“…Juarez suggests that venue-based interventions in shooting galleries may be especially useful for reaching high risk male IDUs in an effort to reduce the spread of blood borne infections. A previous study by our group and other international literature have documented that shooting galleries are closely associated with risky injection practices including the sharing and renting of used syringes (Celentano et al, 1991;Chitwood et al, 1990;Reyes et al, 1996). All of the male IDUs in both study sites reported having shared syringes in shooting galleries.…”
Section: Discussionmentioning
confidence: 76%
“…15,16,[29][30][31] However, in contrast to U.S. studies, needle availability was not a primary reason for SG use, 15,16,[29][30][31] and there was no evidence of needles being rented or indiscriminately shared as found elsewhere. 5,7,8,[10][11][12]30,[32][33][34][35][36][37] Willingness to use MSIC was high among SG users, and MSIC was perceived as an attractive and cost-free alternative to SGs. As found in other SIF feasibility studies, this was conditional on MSIC being near the drug market, low threshold, hygienic, safe from police intervention, and offering assistance in case overdose.…”
Section: Discussionmentioning
confidence: 99%
“…SG use has, however, been associated with increased blood-borne virus (BBV) risk behavior and transmission. [6][7][8][9][10][11][12] The operational and environmental characteristics of SGs, mostly documented in U.S. studies, vary from being anarchic to management by operators with entry fees of cash or small quantities of drugs. [13][14][15][16] The latter type of SG is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses have been detected on needles and syringes including human immunodeficiency virus (HIV) [1][2][3][4][5][6], hepatitis B virus (HBV) [4,7] and hepatitis C virus (HCV) [4,7]. Injecting with used needles and syringes can also lead to other health complications, including tissue damage, skin abscesses and bacterial endocarditis [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%